Preparation method of solar photo-thermal glass

By using modified water-based polyurethane, modified nano-tin oxide antimony and perfluorohexylethylene on solar thermal glass to form a protective layer, the problem of insufficient anti-aging and self-cleaning performance of existing solar thermal glass is solved, and the problem of insufficient anti-aging and self-cleaning performance of existing solar thermal glass is achieved. Higher anti-aging and self-cleaning properties.

CN119430682APending Publication Date: 2025-02-14JIANGSU SIMBA NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411571120.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When used in natural environments, existing solar thermal glasses are susceptible to natural factors such as sun exposure, acid rain, hot and cold impact, sand and dust, hail, etc., resulting in insufficient anti-aging and self-cleaning performance and inconvenient maintenance.

Method used

Using modified water-based polyurethane, modified nanotin oxide antimony and perfluorohexyl ethylene, a protective layer is formed on the glass substrate through spraying and impregnation processes to improve anti-aging and self-cleaning performance.

Benefits of technology

It realizes excellent anti-aging and self-cleaning properties of solar photothermal glass, can resist the influence of ultraviolet rays, improve self-repair and impact resistance, and reduce maintenance needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005120477490000031
    Figure BDA0005120477490000031
  • Figure BDA0005120477490000041
    Figure BDA0005120477490000041
  • Figure BDA0005120477490000043
    Figure BDA0005120477490000043
Patent Text Reader

Abstract

The invention discloses a preparation method of solar photo-thermal glass, and relates to the field of photo-thermal glass. When the solar photo-thermal glass is prepared, nano tin antimony oxide and dopamine react to obtain modified nano tin antimony oxide; the preparation method comprises the following steps: enabling 1, 4-butanediol, double-end hydroxyl polysiloxane, 3-amino propyl triethoxy silane and isophorone diisocyanate to react, so as to obtain modified waterborne polyurethane; uniformly mixing silicon dioxide, aluminum oxide, lithium oxide, zirconium dioxide, titanium dioxide and antimony trioxide, melting and annealing to obtain a glass substrate; the mixed emulsion is sprayed on a glass substrate, and then the glass substrate is soaked in a perfluorohexyl ethylene solution to obtain the solar photo-thermal glass. The prepared solar photo-thermal glass has excellent self-cleaning, self-repairing, impact resistance and aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photothermal glass, and in particular to a method for preparing solar photothermal glass. Background Art

[0002] Energy is an eternal theme. With the development of the times, humans have used a large amount of fossil fuels, which has led to a gradual shortage of fossil fuels, and some harm will be caused when using fossil fuels. For example, acid rain, greenhouse effect, etc. Therefore, finding clean and efficient new energy to replace conventional fossil energy is the development trend now and in the future. Solar energy is the most abundant renewable clean energy on the earth. It is widely distributed and does not produce byproducts that harm the environment. It is the best choice to replace conventional energy. Among them, since photothermal conversion is the most direct and simple way to utilize solar energy technology, it has become one of the research hotspots in solar energy technology.

[0003] Photothermal conversion refers to the process of concentrating solar radiation energy through reflection, absorption or other means and converting it into a sufficiently high temperature, thereby effectively meeting the requirements of different loads. Photothermal conversion material is a material that can efficiently absorb solar energy and convert it into thermal energy. Combining photothermal conversion material with glass to make solar thermal conversion film glass can increase the glass's absorption rate of solar energy, thereby increasing the temperature and reducing energy consumption. Solar thermal glass is usually installed outdoors and directly exposed to the natural environment. It needs to withstand the influence of natural environments such as sunlight exposure, acid rain, hot and cold shocks, dust, hail, and marine climate, and is not convenient for frequent cleaning and maintenance. Therefore, the present invention prepares a solar thermal glass with excellent anti-aging and self-cleaning properties. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing solar thermal glass to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing solar thermal glass. The solar thermal glass is prepared by spraying modified waterborne polyurethane, modified nano antimony tin oxide and deionized water on a glass substrate after being uniformly mixed, and then immersing the mixture in a perfluorohexylethylene solution.

[0007] As an optimization, the glass substrate is obtained by mixing silicon dioxide, aluminum oxide, lithium oxide, zirconium dioxide, titanium dioxide and antimony trioxide and then melt-annealing.

[0008] As an optimization, the modified nano antimony tin oxide is obtained by reacting nano antimony tin oxide and dopamine.

[0009] As an optimization, the nano antimony-doped tin dioxide comes from Hangzhou Jikang New Materials Co., Ltd.

[0010] As an optimization, the modified waterborne polyurethane is obtained by reacting 1,4-butanediol, bihydroxyl polysiloxane, 3-aminopropyltriethoxysilane and isophorone diisocyanate.

[0011] As an optimization, the dual-terminal hydroxyl polysiloxane is obtained by reacting 2,4,6,8-tetramethylcyclotetrasiloxane with 4-vinylbenzeneboronic acid, and then reacting with 2,4,6,8-tetramethylcyclotetrasiloxane and 1,3-bis(hydroxypropyl)tetramethyldisiloxane.

[0012] A method for preparing solar thermal glass comprises the following steps:

[0013] (1) mixing nano antimony tin oxide and tris(hydroxymethylaminomethane) buffer in a mass ratio of 1:(2400-2600), ultrasonically dispersing for 25-35 min, adding a hydrochloric acid solution with a mass fraction of 15%-25%, adjusting the pH value of the solution to 8-9, adding dopamine in an amount of 0.4-0.6 times the mass of the nano antimony tin oxide, stirring at 55-65° C. and 500-600 rpm for 23-25 ​​h, naturally cooling to room temperature and filtering, washing with deionized water for 3-5 times, and drying at 55-65° C. for 8-10 h to obtain modified nano antimony tin oxide;

[0014] (2) 2,4,6,8-tetramethylcyclotetrasiloxane, 4-vinylbenzeneboronic acid, chloroplatinic acid and toluene are mixed in a mass ratio of 1:(2-4):(0.01-0.02):(4-6), stirred in an argon atmosphere at 100-110° C. and 100-200 rpm for 19-21 h, cooled naturally to room temperature, and distilled under reduced pressure to collect a fraction at 135-155° C. to obtain an addition cyclotetrasiloxane; 2,4,6,8-tetramethylcyclotetrasiloxane, an addition cyclotetrasiloxane and 1,3-bis( 2,4,6,8-tetramethylcyclotetrasiloxane is mixed in a mass ratio of 1:(0.9-1.1):(0.2-0.4), stirred at 65-75°C and 100-200 rpm for 10-20 min, trifluoromethylsulfonic acid is added in an amount of 0.01-0.03 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane, and stirring is continued for 5-7 h, anhydrous sodium carbonate is added to adjust the pH to 6-7, and then filtered, and distilled at 105-115°C and 0.1-0.3 MPa for 1-2 h to obtain a dihydroxy-terminated polysiloxane;

[0015] (3) 1,4-butanediol and isophorone diisocyanate are mixed at a molar ratio of 1:(1.5-2.5), dibutyltin dilaurate is added in an amount of 0.01-0.02 times the mass of 1,4-butanediol, and the mixture is stirred for 1-3 hours at 75-85° C. and 200-300 rpm in a nitrogen atmosphere, and a dihydroxy-terminated polysiloxane is added, wherein the molar ratio of the hydroxyl group in the dihydroxy-terminated polysiloxane to the hydroxyl group in 1,4-butanediol is 1:2, and stirring is continued for 2-4 hours. The mixture is cooled to 55-65° C., 3-aminopropyltriethoxysilane is added in an amount of 2-3 times the mass of 1,4-butanediol, stirring is continued for 1-3 hours, and the mixture is naturally cooled to room temperature to obtain a modified waterborne polyurethane;

[0016] (4) Mix 65-75 parts of silicon dioxide, 15-25 parts of aluminum oxide, 4-6 parts of lithium oxide, 2-4 parts of zirconium dioxide, 1-2 parts of titanium dioxide and 0.04-0.06 parts of antimony trioxide by weight, grind in a corundum crucible for 40-50 minutes, move into an electric furnace, heat to 1600-1700° C. at a rate of 4-6° C. / min and keep warm for 2-4 hours, pour into a graphite mold, keep warm at 450-550° C. for 1-3 hours, cool naturally to room temperature, grind and polish, wash with anhydrous ethanol 3-5 times, and dry at 80-90° C. for 6-8 hours to obtain a glass substrate;

[0017] (5) The modified waterborne polyurethane, modified nano-antimony tin oxide and deionized water are mixed in a mass ratio of 1: (0.1-0.2): (0.5-0.7), and high-speed emulsification is performed for 25-35 minutes to obtain a mixed emulsion; the mixed emulsion is sprayed on a glass substrate with a spray gun, and the mixture is allowed to stand at 20-30° C. for 25-35 minutes, and cross-linked at 75-85° C. for 1-2 hours to obtain a slightly cured glass; the slightly cured glass is immersed in a perfluorohexylethylene solution, taken out, hung to air-dry until no liquid drops within 10-20 seconds, and dried at 70-80° C. for 10-12 hours to obtain a solar thermal glass.

[0018] As an optimization, the reaction equation for the modified nano antimony tin oxide in step (1) is:

[0019]

[0020] As an optimization, the reaction equation for adding cyclotetrasiloxane in step (2) is:

[0021]

[0022] Where R is H or As an optimization, the reaction equation of the dihydroxylated polysiloxane in step (2) is:

[0023]

[0024] Where R is H or As an optimization, the reaction equation of the modified waterborne polyurethane in step (3) is:

[0025]

[0026] Where R: R1: R2:

[0027] As an optimization, the perfluorohexylethylene solution in step (5) is obtained by mixing perfluorohexylethylene, chloroplatinic acid and methanol in a mass ratio of 1:0.01:10.

[0028] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0029] When preparing solar thermal glass, the present invention comprises the following steps: reacting nano antimony tin oxide and dopamine to obtain modified nano antimony tin oxide; reacting 2,4,6,8-tetramethylcyclotetrasiloxane and 4-vinylbenzene boronic acid to obtain addition cyclotetrasiloxane; then reacting 2,4,6,8-tetramethylcyclotetrasiloxane, addition cyclotetrasiloxane and 1,3-bis(hydroxypropyl)tetramethyldisiloxane to obtain double-terminal hydroxyl polysiloxane; reacting 1,4-butanediol, double-terminal hydroxyl polysiloxane, 3-aminopropyl triethoxysilane and isophorone diisocyanate to obtain modified waterborne polyurethane; mixing silicon dioxide, aluminum oxide, lithium oxide, zirconium dioxide, titanium dioxide and antimony trioxide, and then performing melt annealing to obtain a glass substrate; mixing the modified waterborne polyurethane, modified nano antimony tin oxide and deionized water, and then spraying the mixture on the glass substrate, and then immersing the mixture in a perfluorohexylethylene solution to obtain the solar thermal glass.

[0030] Firstly, nano antimony tin oxide and dopamine are reacted to obtain modified nano antimony tin oxide; 2,4,6,8-tetramethylcyclotetrasiloxane and 4-vinylphenylboronic acid are reacted to obtain addition cyclotetrasiloxane; then 2,4,6,8-tetramethylcyclotetrasiloxane, addition cyclotetrasiloxane and 1,3-bis(hydroxypropyl)tetramethyldisiloxane are reacted to obtain double-terminated hydroxyl polysiloxane; dopamine is self-polymerized on the surface of nano antimony tin oxide to form a transparent protective layer, which does not affect the transmittance while improving the dispersion of nano antimony tin oxide, resisting the influence of ultraviolet rays, and improving the anti-aging property of solar thermal glass; at the same time, a large amount of phthalic acid in polydopamine The phenol structure can form a dynamic borate ester bond cross-linking network with phenylboronic acid, thereby improving the self-healing and impact resistance of solar thermal glass. By utilizing the hydrosilylation reaction, the phenylboronic acid structure is grafted onto 2,4,6,8-tetramethylcyclotetrasiloxane, and cross-linked with 1,2-diol on polydopamine to form a dynamic reversible five-membered borane ring, thereby enriching the cross-linking network of modified nano-antimony tin oxide and modified waterborne polyurethane, thereby improving the self-healing and impact resistance of solar thermal glass. By synthesizing double-terminated hydroxyl polysiloxane, long silicon-oxygen chains are introduced into the main chain of waterborne polyurethane, thereby improving the surface hydrophobicity and dirt adhesion, and increasing the self-cleaning property of solar thermal glass.

[0031] Secondly, 1,4-butanediol, double-terminated hydroxyl polysiloxane, 3-aminopropyltriethoxysilane and isophorone diisocyanate are reacted to obtain modified waterborne polyurethane; silicon dioxide, aluminum oxide, lithium oxide, zirconium dioxide, titanium dioxide and antimony trioxide are mixed and melt-annealed to obtain a glass substrate; modified waterborne polyurethane, modified nano-tin antimony oxide and deionized water are mixed and sprayed on the glass substrate, and then immersed in a perfluorohexylethylene solution to obtain solar thermal glass; 3-aminopropyltriethoxysilane is used to terminate the waterborne polyurethane to enhance the chemical bond with the glass substrate and improve the impact resistance of the solar thermal glass; by doping titanium dioxide as a nucleus agent, the formation of glass crystal phase is promoted while improving the photothermal conversion effect of ultraviolet rays, thereby improving the impact resistance and anti-aging performance of the solar thermal glass; perfluorohexylethylene is grafted by hydrosilylation reaction to enhance chemical inertness, reduce surface energy, and further improve the self-cleaning property of the solar thermal glass. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] Embodiment 1:

[0034] A method for preparing solar thermal glass, the method for preparing solar thermal glass comprising the following preparation steps:

[0035] (1) Nano antimony tin oxide and tris(hydroxymethylaminomethane) buffer were mixed at a mass ratio of 1:2400, ultrasonically dispersed for 25 min, a 15% hydrochloric acid solution was added, the pH of the solution was adjusted to 8, dopamine (0.4 times the mass of the nano antimony tin oxide) was added, stirred at 55° C. and 500 rpm for 25 h, naturally cooled to room temperature and filtered, washed with deionized water for 3 times, and dried at 55° C. for 10 h to obtain modified nano antimony tin oxide;

[0036] (2) 2,4,6,8-tetramethylcyclotetrasiloxane, 4-vinylbenzeneboronic acid, chloroplatinic acid and toluene were mixed in a mass ratio of 1:2:0.01:4, stirred at 100°C and 100 rpm for 21 hours in an argon atmosphere, cooled naturally to room temperature, and distilled under reduced pressure to collect the fraction at 135°C to obtain addition cyclotetrasiloxane; 2,4,6,8-tetramethylcyclotetrasiloxane, addition cyclotetrasiloxane and 1,3-bis(hydroxypropyl)tetramethyldisiloxane were mixed in a mass ratio of 1:0.9:0.2, stirred at 65°C and 100 rpm for 20 minutes, trifluoromethylsulfonic acid (0.01 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, and stirring was continued for 7 hours. After adding anhydrous sodium carbonate to adjust the pH to 6, the mixture was filtered and distilled at 105°C and 0.1 MPa for 2 hours to obtain a dihydroxy-terminated polysiloxane;

[0037] (3) 1,4-butanediol and isophorone diisocyanate were mixed at a molar ratio of 1:1.5, dibutyltin dilaurate was added at 0.01 times the mass of 1,4-butanediol, and the mixture was stirred at 75°C and 200 rpm for 3 h in a nitrogen atmosphere, and a dihydroxy-terminated polysiloxane was added, wherein the molar ratio of the hydroxyl group in the dihydroxy-terminated polysiloxane to the hydroxyl group in 1,4-butanediol was 1:2, and the mixture was stirred for 4 h. The mixture was cooled to 55°C, 3-aminopropyltriethoxysilane was added at 2 times the mass of 1,4-butanediol, and the mixture was stirred for 3 h. The mixture was naturally cooled to room temperature to obtain a modified waterborne polyurethane.

[0038] (4) 65 parts of silicon dioxide, 15 parts of aluminum oxide, 4 parts of lithium oxide, 2 parts of zirconium dioxide, 1 part of titanium dioxide and 0.04 parts of antimony trioxide were mixed by weight, ground in a corundum crucible for 40 minutes, moved into an electric furnace, heated to 1600°C at a rate of 4°C / min and kept warm for 4 hours, poured into a graphite mold, kept warm at 450°C for 3 hours, naturally cooled to room temperature, polished, washed with anhydrous ethanol 3 times, and dried at 80°C for 8 hours to obtain a glass substrate;

[0039] (5) The modified waterborne polyurethane, modified nano-antimony tin oxide and deionized water were mixed in a mass ratio of 1:0.1:0.5, and the mixture was emulsified at high speed for 25 minutes to obtain a mixed emulsion; the mixed emulsion was sprayed on a glass substrate with a spray gun, allowed to stand at 20°C for 35 minutes, and cross-linked at 75°C for 2 hours to obtain a slightly cured glass; the slightly cured glass was immersed in a perfluorohexylethylene solution and then taken out, hung to air-dry until no liquid dripped within 10 seconds, and dried at 70°C for 12 hours to obtain a solar thermal glass.

[0040] Embodiment 2:

[0041] A method for preparing solar thermal glass, the method for preparing solar thermal glass comprising the following preparation steps:

[0042] (1) Nano antimony tin oxide and tris(hydroxymethylaminomethane) buffer were mixed at a mass ratio of 1:2500, ultrasonically dispersed for 30 min, a 20% hydrochloric acid solution was added, the pH of the solution was adjusted to 8.5, dopamine was added in an amount of 0.5 times the mass of the nano antimony tin oxide, stirred at 60° C. and 550 rpm for 24 h, naturally cooled to room temperature, filtered, washed with deionized water for 4 times, and dried at 60° C. for 9 h to obtain modified nano antimony tin oxide;

[0043] (2) 2,4,6,8-tetramethylcyclotetrasiloxane, 4-vinylbenzeneboronic acid, chloroplatinic acid and toluene were mixed in a mass ratio of 1:3:0.015:5, stirred for 20 hours at 105°C and 150 rpm in an argon atmosphere, cooled naturally to room temperature, and distilled under reduced pressure to collect the fraction at 145°C to obtain addition cyclotetrasiloxane; 2,4,6,8-tetramethylcyclotetrasiloxane, addition cyclotetrasiloxane and 1,3-bis(hydroxypropyl)tetramethyldisiloxane were mixed in a mass ratio of 1:1:0.3, stirred for 15 minutes at 70°C and 150 rpm, trifluoromethylsulfonic acid (0.02 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, and stirring was continued for 6 hours. Anhydrous sodium carbonate was added to adjust the pH to 6.5, and then filtered, and distilled at 110°C and 0.2 MPa for 1.5 hours to obtain a dihydroxy-terminated polysiloxane;

[0044] (3) 1,4-butanediol and isophorone diisocyanate were mixed in a molar ratio of 1:2, dibutyltin dilaurate was added in an amount of 0.015 times the mass of 1,4-butanediol, and the mixture was stirred for 2 h at 80° C. and 250 rpm in a nitrogen atmosphere, and a dihydroxy-terminated polysiloxane was added, wherein the molar ratio of the hydroxyl group in the dihydroxy-terminated polysiloxane to the hydroxyl group in 1,4-butanediol was 1:2, and the mixture was stirred for 3 h. The mixture was cooled to 60° C., 3-aminopropyltriethoxysilane was added in an amount of 2.5 times the mass of 1,4-butanediol, and the mixture was stirred for 2 h. The mixture was naturally cooled to room temperature to obtain a modified waterborne polyurethane.

[0045] (4) 70 parts of silicon dioxide, 20 parts of aluminum oxide, 5 parts of lithium oxide, 3 parts of zirconium dioxide, 1.5 parts of titanium dioxide and 0.05 parts of antimony trioxide were mixed by weight, ground in a corundum crucible for 45 minutes, moved into an electric furnace, heated to 1650°C at a rate of 5°C / min and kept warm for 3 hours, poured into a graphite mold, kept warm at 500°C for 2 hours, naturally cooled to room temperature, polished, washed with anhydrous ethanol 4 times, and dried at 85°C for 7 hours to obtain a glass substrate;

[0046] (5) The modified waterborne polyurethane, modified nano-antimony tin oxide and deionized water were mixed in a mass ratio of 1:0.15:0.6, and the mixture was emulsified at high speed for 30 minutes to obtain a mixed emulsion; the mixed emulsion was sprayed on a glass substrate with a spray gun, allowed to stand at 25°C for 30 minutes, and cross-linked at 80°C for 1.5 hours to obtain a slightly cured glass; the slightly cured glass was immersed in a perfluorohexylethylene solution and then taken out, hung to air-dry until no liquid dripped within 15 seconds, and dried at 75°C for 11 hours to obtain a solar thermal glass.

[0047] Embodiment 3:

[0048] A method for preparing solar thermal glass, the method for preparing solar thermal glass comprising the following preparation steps:

[0049] (1) Nano antimony tin oxide and tris(hydroxymethylaminomethane) buffer were mixed at a mass ratio of 1:2600, ultrasonically dispersed for 35 min, a 25% hydrochloric acid solution was added, the pH of the solution was adjusted to 9, dopamine (0.6 times the mass of the nano antimony tin oxide) was added, stirred at 65° C. and 600 rpm for 23 h, naturally cooled to room temperature and filtered, washed with deionized water for 5 times, and dried at 65° C. for 8 h to obtain modified nano antimony tin oxide;

[0050] (2) 2,4,6,8-tetramethylcyclotetrasiloxane, 4-vinylbenzeneboronic acid, chloroplatinic acid and toluene were mixed in a mass ratio of 1:4:0.02:6, stirred at 110°C and 200 rpm for 19 hours in an argon atmosphere, cooled naturally to room temperature, and distilled under reduced pressure to collect the fraction at 155°C to obtain addition cyclotetrasiloxane; 2,4,6,8-tetramethylcyclotetrasiloxane, addition cyclotetrasiloxane and 1,3-bis(hydroxypropyl)tetramethyldisiloxane were mixed in a mass ratio of 1:1.1:0.4, stirred at 75°C and 200 rpm for 10 minutes, trifluoromethylsulfonic acid (0.03 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, and stirring was continued for 5 hours. Anhydrous sodium carbonate was added to adjust the pH to 7, filtered, and distilled at 115°C and 0.3 MPa for 1 hour to obtain a dihydroxy-terminated polysiloxane;

[0051] (3) 1,4-butanediol and isophorone diisocyanate were mixed at a molar ratio of 1:2.5, dibutyltin dilaurate was added at 0.02 times the mass of 1,4-butanediol, and the mixture was stirred at 85°C and 300 rpm for 1 h in a nitrogen atmosphere, and a dihydroxy-terminated polysiloxane was added, wherein the molar ratio of the hydroxyl group in the dihydroxy-terminated polysiloxane to the hydroxyl group in 1,4-butanediol was 1:2, and the mixture was stirred for 2 h. The mixture was cooled to 65°C, 3-aminopropyltriethoxysilane was added at 3 times the mass of 1,4-butanediol, and the mixture was stirred for 1 h. The mixture was cooled to room temperature to obtain a modified waterborne polyurethane.

[0052] (4) 75 parts of silicon dioxide, 25 parts of aluminum oxide, 6 parts of lithium oxide, 4 parts of zirconium dioxide, 2 parts of titanium dioxide and 0.06 parts of antimony trioxide were mixed by weight, ground in a corundum crucible for 50 min, moved into an electric furnace, heated to 1700°C at a rate of 6°C / min and kept warm for 2 h, poured into a graphite mold, kept warm at 550°C for 1 h, naturally cooled to room temperature, polished, washed with anhydrous ethanol 5 times, and dried at 90°C for 6 h to obtain a glass substrate;

[0053] (5) The modified waterborne polyurethane, modified nano-antimony tin oxide and deionized water were mixed in a mass ratio of 1:0.2:0.7, and the mixture was emulsified at high speed for 35 minutes to obtain a mixed emulsion; the mixed emulsion was sprayed on a glass substrate with a spray gun, allowed to stand at 30°C for 25 minutes, and cross-linked at 85°C for 1 hour to obtain a slightly cured glass; the slightly cured glass was immersed in a perfluorohexylethylene solution and then taken out, hung to air-dry until no liquid dripped within 20 seconds, and dried at 80°C for 10 hours to obtain a solar thermal glass.

[0054] Comparative Example 1:

[0055] A method for preparing solar thermal glass, the method for preparing solar thermal glass comprising the following preparation steps:

[0056] (1) 2,4,6,8-tetramethylcyclotetrasiloxane, 4-vinylbenzeneboronic acid, chloroplatinic acid and toluene were mixed in a mass ratio of 1:3:0.015:5, stirred for 20 hours at 105°C and 150 rpm in an argon atmosphere, cooled naturally to room temperature, and distilled under reduced pressure to collect the fraction at 145°C to obtain addition cyclotetrasiloxane; 2,4,6,8-tetramethylcyclotetrasiloxane, addition cyclotetrasiloxane and 1,3-bis(hydroxypropyl)tetramethyldisiloxane were mixed in a mass ratio of 1:1:0.3, stirred for 15 minutes at 70°C and 150 rpm, trifluoromethylsulfonic acid (0.02 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, and stirring was continued for 6 hours, anhydrous sodium carbonate was added to adjust the pH to 6.5, and then filtered, and distilled at 110°C and 0.2 MPa for 1.5 hours to obtain a dihydroxy-terminated polysiloxane;

[0057] (2) 1,4-butanediol and isophorone diisocyanate were mixed in a molar ratio of 1:2, dibutyltin dilaurate was added in an amount of 0.015 times the mass of 1,4-butanediol, and the mixture was stirred for 2 h at 80° C. and 250 rpm in a nitrogen atmosphere, and a dihydroxy-terminated polysiloxane was added, wherein the molar ratio of the hydroxyl group in the dihydroxy-terminated polysiloxane to the hydroxyl group in 1,4-butanediol was 1:2, and the mixture was stirred for 3 h. The mixture was cooled to 60° C., 3-aminopropyltriethoxysilane was added in an amount of 2.5 times the mass of 1,4-butanediol, and the mixture was stirred for 2 h. The mixture was naturally cooled to room temperature to obtain a modified waterborne polyurethane.

[0058] (3) 70 parts of silicon dioxide, 20 parts of aluminum oxide, 5 parts of lithium oxide, 3 parts of zirconium dioxide, 1.5 parts of titanium dioxide and 0.05 parts of antimony trioxide were mixed by weight, ground in a corundum crucible for 45 minutes, moved into an electric furnace, heated to 1650°C at a rate of 5°C / min and kept warm for 3 hours, poured into a graphite mold, kept warm at 500°C for 2 hours, naturally cooled to room temperature, polished, washed with anhydrous ethanol 4 times, and dried at 85°C for 7 hours to obtain a glass substrate;

[0059] (4) The modified waterborne polyurethane, nano-antimony tin oxide and deionized water were mixed in a mass ratio of 1:0.15:0.6, and the mixture was emulsified at high speed for 30 minutes to obtain a mixed emulsion; the mixed emulsion was sprayed on a glass substrate with a spray gun, allowed to stand at 25°C for 30 minutes, and cross-linked at 80°C for 1.5 hours to obtain a slightly cured glass; the slightly cured glass was immersed in a perfluorohexylethylene solution and then taken out, hung to air-dry until no liquid dripped within 15 seconds, and dried at 75°C for 11 hours to obtain a solar thermal glass.

[0060] Comparative Example 2:

[0061] A method for preparing solar thermal glass, the method for preparing solar thermal glass comprising the following preparation steps:

[0062] (1) Nano antimony tin oxide and tris(hydroxymethylaminomethane) buffer were mixed at a mass ratio of 1:2500, ultrasonically dispersed for 30 min, a 20% hydrochloric acid solution was added, the pH of the solution was adjusted to 8.5, dopamine was added in an amount of 0.5 times the mass of the nano antimony tin oxide, stirred at 60° C. and 550 rpm for 24 h, naturally cooled to room temperature, filtered, washed with deionized water for 4 times, and dried at 60° C. for 9 h to obtain modified nano antimony tin oxide;

[0063] (2) 2,4,6,8-tetramethylcyclotetrasiloxane and 1,3-bis(hydroxypropyl)tetramethyldisiloxane were mixed in a mass ratio of 1:0.3, stirred at 70°C and 150 rpm for 15 min, trifluoromethylsulfonic acid (0.02 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, and stirring was continued for 6 h. Anhydrous sodium carbonate was added to adjust the pH to 6.5, and then filtered, and distilled at 110°C and 0.2 MPa for 1.5 h to obtain a dihydroxy-terminated polysiloxane;

[0064] (3) 1,4-butanediol and isophorone diisocyanate were mixed in a molar ratio of 1:2, dibutyltin dilaurate was added in an amount of 0.015 times the mass of 1,4-butanediol, and the mixture was stirred for 2 h at 80° C. and 250 rpm in a nitrogen atmosphere, and a dihydroxy-terminated polysiloxane was added, wherein the molar ratio of the hydroxyl group in the dihydroxy-terminated polysiloxane to the hydroxyl group in 1,4-butanediol was 1:2, and the mixture was stirred for 3 h. The mixture was cooled to 60° C., 3-aminopropyltriethoxysilane was added in an amount of 2.5 times the mass of 1,4-butanediol, and the mixture was stirred for 2 h. The mixture was naturally cooled to room temperature to obtain a modified waterborne polyurethane.

[0065] (4) 70 parts of silicon dioxide, 20 parts of aluminum oxide, 5 parts of lithium oxide, 3 parts of zirconium dioxide, 1.5 parts of titanium dioxide and 0.05 parts of antimony trioxide were mixed by weight, ground in a corundum crucible for 45 minutes, moved into an electric furnace, heated to 1650°C at a rate of 5°C / min and kept warm for 3 hours, poured into a graphite mold, kept warm at 500°C for 2 hours, naturally cooled to room temperature, polished, washed with anhydrous ethanol 4 times, and dried at 85°C for 7 hours to obtain a glass substrate;

[0066] (5) The modified waterborne polyurethane, modified nano-antimony tin oxide and deionized water were mixed in a mass ratio of 1:0.15:0.6, and the mixture was emulsified at high speed for 30 minutes to obtain a mixed emulsion; the mixed emulsion was sprayed on a glass substrate with a spray gun, allowed to stand at 25°C for 30 minutes, and cross-linked at 80°C for 1.5 hours to obtain a slightly cured glass; the slightly cured glass was immersed in a perfluorohexylethylene solution and then taken out, hung to air-dry until no liquid dripped within 15 seconds, and dried at 75°C for 11 hours to obtain a solar thermal glass.

[0067] Comparative Example 3:

[0068] A method for preparing solar thermal glass, the method for preparing solar thermal glass comprising the following preparation steps:

[0069] (1) Nano antimony tin oxide and tris(hydroxymethylaminomethane) buffer were mixed at a mass ratio of 1:2500, ultrasonically dispersed for 30 min, a 20% hydrochloric acid solution was added, the pH of the solution was adjusted to 8.5, dopamine was added in an amount of 0.5 times the mass of the nano antimony tin oxide, stirred at 60° C. and 550 rpm for 24 h, naturally cooled to room temperature, filtered, washed with deionized water for 4 times, and dried at 60° C. for 9 h to obtain modified nano antimony tin oxide;

[0070] (2) 2,4,6,8-tetramethylcyclotetrasiloxane, 4-vinylbenzeneboronic acid, chloroplatinic acid and toluene were mixed in a mass ratio of 1:3:0.015:5, stirred for 20 hours at 105°C and 150 rpm in an argon atmosphere, cooled naturally to room temperature, and distilled under reduced pressure to collect the fraction at 145°C to obtain addition cyclotetrasiloxane; 2,4,6,8-tetramethylcyclotetrasiloxane, addition cyclotetrasiloxane and 1,3-bis(hydroxypropyl)tetramethyldisiloxane were mixed in a mass ratio of 1:1:0.3, stirred for 15 minutes at 70°C and 150 rpm, trifluoromethylsulfonic acid (0.02 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, and stirring was continued for 6 hours. Anhydrous sodium carbonate was added to adjust the pH to 6.5, and then filtered, and distilled at 110°C and 0.2 MPa for 1.5 hours to obtain a dihydroxy-terminated polysiloxane;

[0071] (3) 1,4-butanediol and isophorone diisocyanate were mixed in a molar ratio of 1:2, dibutyltin dilaurate was added in an amount of 0.015 times the mass of 1,4-butanediol, and the mixture was stirred for 2 h at 80° C. and 250 rpm in a nitrogen atmosphere, and a dihydroxy-terminated polysiloxane was added, wherein the molar ratio of the hydroxyl group in the dihydroxy-terminated polysiloxane to the hydroxyl group in 1,4-butanediol was 1:2, and the mixture was stirred for 3 h. The mixture was cooled to 60° C., 3-aminopropyltriethoxysilane was added in an amount of 2.5 times the mass of 1,4-butanediol, and the mixture was stirred for 2 h. The mixture was naturally cooled to room temperature to obtain a modified waterborne polyurethane.

[0072] (4) 70 parts of silicon dioxide, 20 parts of aluminum oxide, 5 parts of lithium oxide, 3 parts of zirconium dioxide, 1.5 parts of titanium dioxide and 0.05 parts of antimony trioxide were mixed by weight, ground in a corundum crucible for 45 minutes, moved into an electric furnace, heated to 1650°C at a rate of 5°C / min and kept warm for 3 hours, poured into a graphite mold, kept warm at 500°C for 2 hours, naturally cooled to room temperature, polished, washed with anhydrous ethanol 4 times, and dried at 85°C for 7 hours to obtain a glass substrate;

[0073] (5) The modified waterborne polyurethane, modified nano-antimony tin oxide and deionized water were mixed in a mass ratio of 1:0.15:0.6, and high-speed emulsification was performed for 30 minutes to obtain a mixed emulsion; the mixed emulsion was sprayed on a glass substrate with a spray gun, allowed to stand at 25°C for 30 minutes, and dried at 75°C for 11 hours to obtain solar thermal glass.

[0074] Comparative Example 4:

[0075] A method for preparing solar thermal glass, the method for preparing solar thermal glass comprising the following preparation steps:

[0076] (1) Nano antimony tin oxide and tris(hydroxymethylaminomethane) buffer were mixed at a mass ratio of 1:2500, ultrasonically dispersed for 30 min, a 20% hydrochloric acid solution was added, the pH of the solution was adjusted to 8.5, dopamine was added in an amount of 0.5 times the mass of the nano antimony tin oxide, stirred at 60° C. and 550 rpm for 24 h, naturally cooled to room temperature, filtered, washed with deionized water for 4 times, and dried at 60° C. for 9 h to obtain modified nano antimony tin oxide;

[0077] (2) 1,4-butanediol and isophorone diisocyanate were mixed at a molar ratio of 1:2, dibutyltin dilaurate (0.015 times the mass of 1,4-butanediol) was added, and the mixture was stirred at 80°C and 250 rpm for 2 h in a nitrogen atmosphere, cooled to 60°C, 3-aminopropyltriethoxysilane (2.5 times the mass of 1,4-butanediol) was added, and the mixture was stirred for 2 h, and naturally cooled to room temperature to obtain a modified waterborne polyurethane;

[0078] (3) 70 parts of silicon dioxide, 20 parts of aluminum oxide, 5 parts of lithium oxide, 3 parts of zirconium dioxide, 1.5 parts of titanium dioxide and 0.05 parts of antimony trioxide were mixed by weight, ground in a corundum crucible for 45 minutes, moved into an electric furnace, heated to 1650°C at a rate of 5°C / min and kept warm for 3 hours, poured into a graphite mold, kept warm at 500°C for 2 hours, naturally cooled to room temperature, polished, washed with anhydrous ethanol 4 times, and dried at 85°C for 7 hours to obtain a glass substrate;

[0079] (4) The modified waterborne polyurethane, modified nano-antimony tin oxide and deionized water were mixed in a mass ratio of 1:0.15:0.6, and the mixture was emulsified at high speed for 30 minutes to obtain a mixed emulsion; the mixed emulsion was sprayed on a glass substrate with a spray gun, allowed to stand at 25°C for 30 minutes, and cross-linked at 80°C for 1.5 hours to obtain a slightly cured glass; the slightly cured glass was immersed in a perfluorohexylethylene solution and then taken out, hung to air-dry until no liquid dripped within 15 seconds, and dried at 75°C for 11 hours to obtain a solar thermal glass.

[0080] Comparative Example 5:

[0081] A method for preparing solar thermal glass, the method for preparing solar thermal glass comprising the following preparation steps:

[0082] (1) Nano antimony tin oxide and tris(hydroxymethylaminomethane) buffer were mixed at a mass ratio of 1:2500, ultrasonically dispersed for 30 min, a 20% hydrochloric acid solution was added, the pH of the solution was adjusted to 8.5, dopamine was added in an amount of 0.5 times the mass of the nano antimony tin oxide, stirred at 60° C. and 550 rpm for 24 h, naturally cooled to room temperature, filtered, washed with deionized water for 4 times, and dried at 60° C. for 9 h to obtain modified nano antimony tin oxide;

[0083] (2) 2,4,6,8-tetramethylcyclotetrasiloxane, 4-vinylbenzeneboronic acid, chloroplatinic acid and toluene were mixed in a mass ratio of 1:3:0.015:5, stirred for 20 hours at 105°C and 150 rpm in an argon atmosphere, cooled naturally to room temperature, and distilled under reduced pressure to collect the fraction at 145°C to obtain addition cyclotetrasiloxane; 2,4,6,8-tetramethylcyclotetrasiloxane, addition cyclotetrasiloxane and 1,3-bis(hydroxypropyl)tetramethyldisiloxane were mixed in a mass ratio of 1:1:0.3, stirred for 15 minutes at 70°C and 150 rpm, trifluoromethylsulfonic acid (0.02 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, and stirring was continued for 6 hours. Anhydrous sodium carbonate was added to adjust the pH to 6.5, and then filtered, and distilled at 110°C and 0.2 MPa for 1.5 hours to obtain a dihydroxy-terminated polysiloxane;

[0084] (3) 1,4-butanediol and isophorone diisocyanate were mixed in a molar ratio of 1:2, dibutyltin dilaurate was added in an amount of 0.015 times the mass of 1,4-butanediol, and the mixture was stirred for 2 h at 80° C. and 250 rpm in a nitrogen atmosphere, and a dihydroxy-terminated polysiloxane was added, wherein the molar ratio of the hydroxyl group in the dihydroxy-terminated polysiloxane to the hydroxyl group in 1,4-butanediol was 1:2, and the mixture was stirred for 3 h, and the mixture was naturally cooled to room temperature to obtain a modified waterborne polyurethane;

[0085] (4) 70 parts of silicon dioxide, 20 parts of aluminum oxide, 5 parts of lithium oxide, 3 parts of zirconium dioxide, 1.5 parts of titanium dioxide and 0.05 parts of antimony trioxide were mixed by weight, ground in a corundum crucible for 45 minutes, moved into an electric furnace, heated to 1650°C at a rate of 5°C / min and kept warm for 3 hours, poured into a graphite mold, kept warm at 500°C for 2 hours, naturally cooled to room temperature, polished, washed with anhydrous ethanol 4 times, and dried at 85°C for 7 hours to obtain a glass substrate;

[0086] (5) The modified waterborne polyurethane, modified nano-antimony tin oxide and deionized water were mixed in a mass ratio of 1:0.15:0.6, and the mixture was emulsified at high speed for 30 minutes to obtain a mixed emulsion; the mixed emulsion was sprayed on a glass substrate with a spray gun, allowed to stand at 25°C for 30 minutes, and cross-linked at 80°C for 1.5 hours to obtain a slightly cured glass; the slightly cured glass was immersed in a perfluorohexylethylene solution and then taken out, hung to air-dry until no liquid dripped within 15 seconds, and dried at 75°C for 11 hours to obtain a solar thermal glass.

[0087] Comparative Example 6:

[0088] A method for preparing solar thermal glass, the method for preparing solar thermal glass comprising the following preparation steps:

[0089] (1) Nano antimony tin oxide and tris(hydroxymethylaminomethane) buffer were mixed at a mass ratio of 1:2500, ultrasonically dispersed for 30 min, a 20% hydrochloric acid solution was added, the pH of the solution was adjusted to 8.5, dopamine was added in an amount of 0.5 times the mass of the nano antimony tin oxide, stirred at 60° C. and 550 rpm for 24 h, naturally cooled to room temperature, filtered, washed with deionized water for 4 times, and dried at 60° C. for 9 h to obtain modified nano antimony tin oxide;

[0090] (2) 2,4,6,8-tetramethylcyclotetrasiloxane, 4-vinylbenzeneboronic acid, chloroplatinic acid and toluene were mixed in a mass ratio of 1:3:0.015:5, stirred for 20 hours at 105°C and 150 rpm in an argon atmosphere, cooled naturally to room temperature, and distilled under reduced pressure to collect the fraction at 145°C to obtain addition cyclotetrasiloxane; 2,4,6,8-tetramethylcyclotetrasiloxane, addition cyclotetrasiloxane and 1,3-bis(hydroxypropyl)tetramethyldisiloxane were mixed in a mass ratio of 1:1:0.3, stirred for 15 minutes at 70°C and 150 rpm, trifluoromethylsulfonic acid (0.02 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane) was added, and stirring was continued for 6 hours. Anhydrous sodium carbonate was added to adjust the pH to 6.5, and then filtered, and distilled at 110°C and 0.2 MPa for 1.5 hours to obtain a dihydroxy-terminated polysiloxane;

[0091] (3) 1,4-butanediol and isophorone diisocyanate were mixed in a molar ratio of 1:2, dibutyltin dilaurate was added in an amount of 0.015 times the mass of 1,4-butanediol, and the mixture was stirred for 2 h at 80° C. and 250 rpm in a nitrogen atmosphere, and a dihydroxy-terminated polysiloxane was added, wherein the molar ratio of the hydroxyl group in the dihydroxy-terminated polysiloxane to the hydroxyl group in 1,4-butanediol was 1:2, and the mixture was stirred for 3 h. The mixture was cooled to 60° C., 3-aminopropyltriethoxysilane was added in an amount of 2.5 times the mass of 1,4-butanediol, and the mixture was stirred for 2 h. The mixture was naturally cooled to room temperature to obtain a modified waterborne polyurethane.

[0092] (4) 70 parts of silicon dioxide, 20 parts of aluminum oxide, 5 parts of lithium oxide, 3 parts of zirconium dioxide and 0.05 parts of antimony trioxide were mixed by weight, ground in a corundum crucible for 45 minutes, moved into an electric furnace, heated to 1650°C at a rate of 5°C / min and kept warm for 3 hours, poured into a graphite mold, kept warm at 500°C for 2 hours, naturally cooled to room temperature, polished, washed with anhydrous ethanol 4 times, and dried at 85°C for 7 hours to obtain a glass substrate;

[0093] (5) The modified waterborne polyurethane, modified nano-antimony tin oxide and deionized water were mixed in a mass ratio of 1:0.15:0.6, and the mixture was emulsified at high speed for 30 minutes to obtain a mixed emulsion; the mixed emulsion was sprayed on a glass substrate with a spray gun, allowed to stand at 25°C for 30 minutes, and cross-linked at 80°C for 1.5 hours to obtain a slightly cured glass; the slightly cured glass was immersed in a perfluorohexylethylene solution and then taken out, hung to air-dry until no liquid dripped within 15 seconds, and dried at 75°C for 11 hours to obtain a solar thermal glass.

[0094] Test Case

[0095] 1. Self-cleaning performance

[0096] Test method: Take the same mass of carbon powder as the pollutant and evenly spread it on the solar thermal glass obtained in each embodiment and comparative example, use a dropper to absorb a small amount of water and drop it on the carbon powder, wait for the water droplets to sit still on the sample glass, tilt the sample glass to observe the water marks and the carbon powder residue on the sample surface.

[0097] 2. Anti-aging performance

[0098] Test method: Take samples of the same size as the solar thermal glass obtained in each embodiment and the comparative example, measure the transmittance T0, place them in a UV aging box, and irradiate the sample surface with UV radiation that meets the requirements of IEC61215 until the UV radiation with a wavelength in the range of 280nm to 400nm reaches 121.0kWh / m 2 , measure the transmittance T1 again, and calculate the transmittance retention rate = T1 / T0*100%.

[0099] 3. Self-healing performance

[0100] Test method: Take samples of the same size from the solar thermal glass obtained in each embodiment and the comparative example, measure the water contact angle θ0, use a razor blade to scratch the sample to simulate a crack, the width of the scratch is about 10μm, and the depth is to the glass substrate. Let it stand at 30°C for 24h, measure the water contact angle θ1 again, and calculate the contact angle reduction rate = θ0-θ1 / θ0*100%.

[0101] 4. Impact resistance

[0102] Test method: Take samples of the same size from the solar thermal glass obtained in each embodiment and the comparative example, fix them in a bracket with a hollow bottom at room temperature, and test them using a laminated glass impact tester (SHALA-KCJ-28). After a 50g steel ball is repeatedly dropped from a height of 110cm, the number of times the ball is dropped when cracks are formed on the glass surface is measured.

[0103] Table 1 below shows the analysis results of the self-cleaning, self-repairing, impact resistance and aging resistance of the solar thermal glass of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.

[0104] Table 1

[0105] Water marks and stains Transmittance retention% Contact angle reduction rate % Number of ball drops Example 1 No water marks or stains 93.6 1.8 5 times Example 2 No water marks or stains 93.9 1.4 5 times Example 3 No water marks or stains 93.8 1.6 5 times Comparative Example 1 No water marks or stains 82.6 23.7 3 times Comparative Example 2 No water marks or stains 93.5 22.9 3 times Comparative Example 3 Minor water stains 92.7 2.5 5 times Comparative Example 4 Lots of water stains 90.2 24.1 2 times Comparative Example 5 No water marks or stains 93.4 2.2 4 times Comparative Example 6 No water marks or stains 81.3 1.9 4 times

[0106] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the solar thermal glass prepared by the present invention has good self-cleaning, self-repairing, impact resistance and aging resistance.

[0107] By comparison, compared with Example 1, Examples 1, 2, and 3 have a higher transmittance retention rate, a lower contact angle reduction rate, and a higher number of ball drops, which illustrates that a transparent protective layer is formed on the surface of nano-antimony tin oxide through self-polymerization of dopamine, which does not affect the transmittance while improving the dispersibility of nano-antimony tin oxide, resisting the influence of ultraviolet rays, and improving the aging resistance of solar thermal glass; at the same time, a large number of catechol structures in polydopamine can form a dynamic borate ester bond cross-linking network with phenylboric acid, thereby improving the self-repairing performance and impact resistance of solar thermal glass.

[0108] By comparison, compared with Example 2, Examples 1, 2, and 3 have a lower contact angle reduction rate and a higher number of ball drops, which illustrates the use of hydrosilylation reaction to graft phenylboronic acid structure on 2,4,6,8-tetramethylcyclotetrasiloxane, cross-link with 1,2-diol on polydopamine to form a dynamically reversible five-membered borane ring, enrich the cross-linking network of modified nano-antimony tin oxide and modified water-based polyurethane, and improve the self-healing performance and impact resistance of solar thermal glass.

[0109] By comparison, Examples 1, 2, and 3 have no water marks or stains compared to Comparative Example 3, which illustrates that the use of hydrosilylation reaction to graft perfluorohexylethylene can enhance chemical inertness, reduce surface energy, and improve the self-cleaning property of solar thermal glass.

[0110] By comparison, compared with Example 4, Examples 1, 2, and 3 have a lower contact angle reduction rate, more ball drops, and no water marks or stains, which indicates that by synthesizing dihydroxyl polysiloxane and introducing long silicon oxygen chains into the main chain of water-based polyurethane, the surface hydrophobicity and dirt adhesion are improved, thereby increasing the self-cleaning property of solar thermal glass.

[0111] By comparison, the ball drops of Examples 1, 2 and 3 are more than those of Comparative Example 5, which indicates that the chemical bond with the glass substrate is enhanced by using 3-aminopropyltriethoxysilane to improve the impact resistance of the solar thermal glass.

[0112] By comparison, Examples 1, 2, and 3 have higher light transmittance retention and more ball drops than Example 6, which indicates that by doping titanium dioxide as a nucleus agent, the formation of glass crystal phase is promoted while the photothermal conversion effect of ultraviolet rays is improved, thereby improving the impact resistance and anti-aging performance of solar thermal glass.

[0113] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing solar thermal glass, characterized in that: The solar thermal glass is prepared by mixing modified waterborne polyurethane, modified nano-tin antimony oxide and deionized water, spraying the mixture on a glass substrate, and then immersing the mixture in a perfluorohexylethylene solution. The glass substrate is obtained by mixing silicon dioxide, aluminum oxide, lithium oxide, zirconium dioxide, titanium dioxide and antimony trioxide and then melting and annealing. The modified nano antimony tin oxide is obtained by reacting nano antimony tin oxide and dopamine; The modified waterborne polyurethane is obtained by reacting 1,4-butanediol, dihydroxyl-terminated polysiloxane, 3-aminopropyltriethoxysilane and isophorone diisocyanate; The dual-terminal hydroxyl polysiloxane is obtained by reacting 2,4,6,8-tetramethylcyclotetrasiloxane with 4-vinylbenzene boronic acid and then with 2,4,6,8-tetramethylcyclotetrasiloxane and 1,3-bis(hydroxypropyl)tetramethyldisiloxane.

2. A method for preparing solar thermal glass according to claim 1, characterized in that: The method comprises the following preparation steps: (1) mixing nano antimony tin oxide and tris(hydroxymethylaminomethane) buffer in a mass ratio of 1:(2400-2600), ultrasonically dispersing for 25-35 min, adding a hydrochloric acid solution with a mass fraction of 15%-25%, adjusting the pH value of the solution to 8-9, adding dopamine in an amount of 0.4-0.6 times the mass of the nano antimony tin oxide, stirring at 55-65° C. and 500-600 rpm for 23-25 ​​h, naturally cooling to room temperature and filtering, washing with deionized water for 3-5 times, and drying at 55-65° C. for 8-10 h to obtain modified nano antimony tin oxide; (2) 2,4,6,8-tetramethylcyclotetrasiloxane, 4-vinylbenzeneboronic acid, chloroplatinic acid and toluene are mixed in a mass ratio of 1:(2-4):(0.01-0.02):(4-6), stirred in an argon atmosphere at 100-110° C. and 100-200 rpm for 19-21 h, cooled naturally to room temperature, and distilled under reduced pressure to collect a fraction at 135-155° C. to obtain an addition cyclotetrasiloxane; 2,4,6,8-tetramethylcyclotetrasiloxane, an addition cyclotetrasiloxane and 1,3-bis( 2,4,6,8-tetramethylcyclotetrasiloxane is mixed in a mass ratio of 1:(0.9-1.1):(0.2-0.4), stirred at 65-75°C and 100-200 rpm for 10-20 min, trifluoromethylsulfonic acid is added in an amount of 0.01-0.03 times the mass of 2,4,6,8-tetramethylcyclotetrasiloxane, and stirring is continued for 5-7 h, anhydrous sodium carbonate is added to adjust the pH to 6-7, and then filtered, and distilled at 105-115°C and 0.1-0.3 MPa for 1-2 h to obtain a dihydroxy-terminated polysiloxane; (3) 1,4-butanediol and isophorone diisocyanate are mixed at a molar ratio of 1:(1.5-2.5), dibutyltin dilaurate is added in an amount of 0.01-0.02 times the mass of 1,4-butanediol, and the mixture is stirred for 1-3 hours at 75-85° C. and 200-300 rpm in a nitrogen atmosphere, and a dihydroxy-terminated polysiloxane is added, wherein the molar ratio of the hydroxyl group in the dihydroxy-terminated polysiloxane to the hydroxyl group in 1,4-butanediol is 1:2, and stirring is continued for 2-4 hours. The mixture is cooled to 55-65° C., 3-aminopropyltriethoxysilane is added in an amount of 2-3 times the mass of 1,4-butanediol, stirring is continued for 1-3 hours, and the mixture is naturally cooled to room temperature to obtain a modified waterborne polyurethane; (4) Mix 65-75 parts of silicon dioxide, 15-25 parts of aluminum oxide, 4-6 parts of lithium oxide, 2-4 parts of zirconium dioxide, 1-2 parts of titanium dioxide and 0.04-0.06 parts of antimony trioxide by weight, grind in a corundum crucible for 40-50 minutes, move into an electric furnace, heat to 1600-1700° C. at a rate of 4-6° C. / min and keep warm for 2-4 hours, pour into a graphite mold, keep warm at 450-550° C. for 1-3 hours, cool naturally to room temperature, grind and polish, wash with anhydrous ethanol 3-5 times, and dry at 80-90° C. for 6-8 hours to obtain a glass substrate; (5) The modified waterborne polyurethane, modified nano-antimony tin oxide and deionized water are mixed in a mass ratio of 1: (0.1-0.2): (0.5-0.7), and high-speed emulsification is performed for 25-35 minutes to obtain a mixed emulsion; the mixed emulsion is sprayed on a glass substrate with a spray gun, and the mixture is allowed to stand at 20-30° C. for 25-35 minutes, and cross-linked at 75-85° C. for 1-2 hours to obtain a slightly cured glass; the slightly cured glass is immersed in a perfluorohexylethylene solution, taken out, hung to air-dry until no liquid drops within 10-20 seconds, and dried at 70-80° C. for 10-12 hours to obtain a solar thermal glass.

3. The method for preparing solar thermal glass according to claim 2, characterized in that: The reaction equation for the modified nano antimony tin oxide in step (1) is:

4. The method for preparing solar thermal glass according to claim 2, characterized in that: The reaction equation for adding cyclotetrasiloxane in step (2) is: Where R is H or 5. The method for preparing solar thermal glass according to claim 2, characterized in that: The reaction equation of the dihydroxy-terminated polysiloxane in step (2) is: Where R is H or 6. The method for preparing solar thermal glass according to claim 2, characterized in that: The reaction equation of the modified waterborne polyurethane in step (3) is: Where R: R1: R2:

7. The method for preparing solar thermal glass according to claim 2, characterized in that: The perfluorohexylethylene solution in step (5) is obtained by mixing perfluorohexylethylene, chloroplatinic acid and methanol in a mass ratio of 1:0.01:10.